Infusion PCTS syntax in the implementation of the middle school science curriculum - Nia Kurniawati; Rudi Susilana; Budi Setiawan (Inovasi Kurikulum, 2024)
Curriculum implementation is an important stage in supporting the success of a curriculum designed by educational institutions. This research aims to apply the PCTS syntax in one of the science learning materials in junior high schools. PCTS is a learning model that focuses on improving students' critical thinking abilities through solving contextual problems. The method used in this research is a qualitative method using a descriptive approach. Data was collected through document study. Data analysis techniques through reduction, presentation, and conclusion. The findings obtained are that the PCTS model is quite easy to apply to science learning as a form of curriculum implementation, and is very supportive of improving students' critical thinking through the PCTS syntax, especially in the last two steps of the syntax. The conclusion is that the PCTS model is believed to support the implementation of the Merdeka Science Curriculum for Middle Schools in improving the critical thinking of individual students through the infusion of PCTS model syntax in science learning at the middle school level.   Abstrak Implementasi kurikulum merupakan tahapan penting dalam menunjang keberhasilan suatu kurikulum yang dirancang oleh institusi pendidikan. Tujuan penelitian ini adalah untuk mengaplikasikan syntax PCTS dalam salah satu materi pembelajaran IPA di SMP. PCTS merupakan model pembelajaran yang berfokus pada peningkatan kemampuan berfikir kritis siswa melalui penyelesaian masalah kontekstual. Metode yang digunakan dalam penelitian ini yaitu metode kualitatif menggunakan pendekatan deskriptif. Data dikumpulkan melalui study dokumen. Teknik analisis data melalui reduksi, penyajian dan penarikan kesimpulan. Temuan yang didapat yaitu model PCTS ini cukup mudah diaplikasikan kedalam pembelajaran IPA sebagai bentuk implementasi kurikulum, dan sangat mendukung terhadap peningkatan critical thinking siswa melalui syntax PCTS, khusunya pada dua langkah terakhir syntax tersebut. Kesimpulannya bahwa Model PCTS ini diyakini akan mendukung implementasi Kurikulum Merdeka IPA SMP dalam meningkatkan critical thinking siswa secara individu melalui infusi syntax model PCTS dalam pembelajaran IPA tingkat SMP. Kata kunci: Critical thinking; implementasi kurikulum; model PCTS; pembelajaran IPA